The economic burden of antibiotic resistance: A systematic review and meta-analysis. - Ak Narayan Poudel; Shihua Zhu; Nicola Cooper; Paul Little; Carolyn Tarrant; Matthew Hickman; Guiqing Yao (PLoS ONE)
Introduction Antibiotic resistance (ABR) has substantial global public health concerns. This systematic review aimed to synthesise recent evidence estimating the economic burden of ABR, characterised by study perspectives, healthcare settings, study design, and income of the countries. Methods This systematic review included peer-reviewed articles from PubMed, Medline, and Scopus databases, and grey literature on the topic of the economic burden of ABR, published between January 2016 and December 2021. The study was reported in line with 'Preferred Reporting Items for Systematic Review and Meta-Analysis' (PRISMA). Two reviewers independently screened papers for inclusion first by title, then abstract, and then the full text. Study quality was assessed using appropriate quality assessment tools. Narrative synthesis and meta-analyses of the included studies were conducted. Results A total of 29 studies were included in this review. Out of these studies, 69% (20/29) were conducted in high-income economies and the remainder were conducted in upper-and-middle income economies. Most of the studies were conducted from a healthcare or hospital perspective (89.6%, 26/29) and 44.8% (13/29) studies were conducted in tertiary care settings. The available evidence indicates that the attributable cost of resistant infection ranges from -US$2,371.4 to +US$29,289.1 (adjusted for 2020 price) per patient episode; the mean excess length of stay (LoS) is 7.4 days (95% CI: 3.4-11.4), the odds ratios of mortality for resistant infection is 1.844 (95% CI: 1.187-2.865) and readmission is 1.492 (95% CI: 1.231-1.807). Conclusion Recent publications show that the burden of ABR is substantial. There is still a lack of studies on the economic burden of ABR from low-income economies, and lower-middle-income economies, from a societal perspective, and in relation to primary care. The findings of this review may be of value to researchers, policymakers, clinicians, and those who are working in the field of ABR and health promotion. Systematic review registration CRD42020193886.